Implementasi Metode Lean Startup dalam Pengembangan Ide Bisnis Aplikasi Golek Kost Berbasis Mobile - Kafita Wardhahani; Erika Ramadhani (Jurnal Sistem Komputer dan Informatika (JSON), 2022)
The need for housing (boarding houses) for students is a basic need and becomes a significant consideration when deciding to study in a particular city. So far, students have obtained information related to boarding houses manually to meet the needs associated with the necessary furniture and in carrying out the moving process. With everything still manual, it takes longer and is more difficult to find a boarding house that fits the student’s needs. To help solve existing problems, a mobile-based application called GOLEK KOST was made. The application is a form of digital innovation to make it easier for students to obtain information related to boarding houses, including prices, locations and boarding facilities, buying, and selling furniture, transportation services, or moving services in the Yogyakarta area. Developing this application business idea applies the Lean Startup method, which consists of three stages: Market Validation, Product Validation, and Business Validation. This method focuses on developing applications based on feedback obtained from potential users so that later the resulting application will meet the needs of potential users. In the product validation, the results obtained are 37% for the boarding information feature, 33.3% for the transportation service feature, and 29.6% for the furniture sale and purchase quality.